Implementation of the Rabies Prevention Program in Efforts to Handle and Prevent Rabies Transmitted Animal Bites in Padang City - Kharina Aprilia; Syamsir (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Health development is directed to eradicate infectious diseases from animals, such as rabies. The Indonesian government is targeting the elimination of rabies in humans due to bites from Rabies-Transmitting Animals (HPR) by 2030, with a requirement that at least 70% of the HPR population be vaccinated. Padang City faces major challenges in controlling rabies, such as increasing cases of HPR bites, limited vaccination, low public awareness, lack of human resources, and suboptimal implementation of the One Health concept. This study aims to determine the implementation of the rabies prevention program and the factors that influence it in Padang City. The study used a descriptive qualitative approach with data collection techniques through interviews, documentation, and source triangulation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of the program had not been optimal due to limited human resources, budget, and low community participation. The obstacles faced include internal factors such as lack of budget and human resources, as well as external factors such as difficulty in adjusting the socialization schedule and low community participation.